2022
DOI: 10.1186/s12915-022-01447-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic characterization of seed overlap microRNA cotargeting associated with lupus pathogenesis

Abstract: Background Combinatorial gene regulation by multiple microRNAs (miRNAs) is widespread and closely spaced target sites often act cooperatively to achieve stronger repression (“neighborhood” miRNA cotargeting). While miRNA cotarget sites are suggested to be more conserved and implicated in developmental control, the pathological significance of miRNA cotargeting remains elusive. Results Here, we report the pathogenic impacts of combinatorial miRNA re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…In addition, we recently reported the systematic characterization of another type of miRNA cotargeting, "seed overlap" miRNA cotargeting (Figure 4b) [100]. We previously reported that downregulation of two miRNAs, miR-128 and miR-148a, additively alters their target KLF4 via extensive overlapping of target sites, leading to enhancement of the inflammatory responses in plasmacytoid dendritic cells in the systemic lupus erythematosus (SLE) mouse model [100].…”
Section: Significance Of Mirna Cotargetingmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, we recently reported the systematic characterization of another type of miRNA cotargeting, "seed overlap" miRNA cotargeting (Figure 4b) [100]. We previously reported that downregulation of two miRNAs, miR-128 and miR-148a, additively alters their target KLF4 via extensive overlapping of target sites, leading to enhancement of the inflammatory responses in plasmacytoid dendritic cells in the systemic lupus erythematosus (SLE) mouse model [100].…”
Section: Significance Of Mirna Cotargetingmentioning
confidence: 99%
“…In addition, we recently reported the systematic characterization of another type of miRNA cotargeting, "seed overlap" miRNA cotargeting (Figure 4b) [100]. We previously reported that downregulation of two miRNAs, miR-128 and miR-148a, additively alters their target KLF4 via extensive overlapping of target sites, leading to enhancement of the inflammatory responses in plasmacytoid dendritic cells in the systemic lupus erythematosus (SLE) mouse model [100]. Although conserved "seed overlap" sites cannot be bound by two miRNAs simultaneously, in contrast to two closely spaced target sites, conserved "seed overlap" sites increase susceptibility to overall downregulation by two distinct miRNAs through additive recruitment of two miRNAs to these sites at the transcriptome level.…”
Section: Significance Of Mirna Cotargetingmentioning
confidence: 99%
See 3 more Smart Citations